Behavior Analysis: Contributions to School Psychology (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
This paper presents potential contributions of Behavior Analysis to School Psychology. We discuss B.F. Skinner´s critical analyses of some of the broader educational issues of his time which are still relevant to contemporary issues faced by school psychologists. We then offer examples of how the behavioral-analytical approach translates into the practice of school psychologist. We hope to contribute to an improvement in the dialogue between behavior analysis and school psychology, which is still incipient in the Brazilian context .
Keywords: behavior analysis; school psychology; education